Analisis Data Kementrian Agama Kota Bitung Menggunakan Metode Data Science - Olivia Manabung; V P Rantung (Ikatan Ahli Informatika Indonesia, 2023)
The Ministry of Religion (Kemenag) of the Republic of Indonesia was born on January 3 1946, the Ministry of Religion is the ministry tasked with assisting the government in the field of religion. In this research, researchers will predict the number of people for each religion in the next two years using data on the number of people from several years ago using the ARIMA Time Series forecasting method using the EView 12 application and researchers will also group places of worship based on sub-district religions using Clutering. K-Means uses the RapidMiner application to see the number of places of worship for each religion in each sub-district. The aim of this research is to help the Ministry of Religion of Bitung City in creating a dashboard to display data information and data reports about the number of people in each religion, predicting the number of people in the next two years, grouping places of worship for each religion, and the number of places of worship for each religion in the city of Bitung. The results obtained from the prediction of the number of Catholics in the city of Bitung in 2023 will be 5,563 people and in 2024 there will be 5,301 people, the predicted number of people from the Islamic religion in 2023 will be 32,768 people and in 2024 there will be 29,988 people, and the results are obtained from the prediction of the number of people from the christianity in the city of Bitung in 2023 there will be 113,242 people and in 2024 there will be 134,433 people. This produces 3 cluster models containing cluster 0 4 items, cluster 1 3 items, and cluster 2 1 items. The cluster starts from the number 0 because when discussing programming the number 0 is the first number in the numbering sequence